Protection and management of castles' and castle ruins' surroundings - Pałubska, Katarzyna (Protection of Cultural Heritage, 2023)
Castles and historical ruins of castles are undoubted testimony to the interaction between man and nature. The historical value is emphasized by their picturesqueness, which at the same time indicates the great attractiveness of the cultural landscape. Old spatial relations built local and regional identity – old transportation routes connecting markers in the form of towers of castles and churches gave a sense of security to travelers of the time, and were distinctive features of a unified landscape. At the same time, distant view openings of several kilometers and several kilometers from the castle extending far out into the surrounding landscape, beyond the boundaries of the hill/area where the castle itself was located, had a regional character, providing security and control, giving insight into distant spatial relations, resulting from historical political dependencies, economic, social and communication relations.